Selected Heavy Metals Concentration in Maize Grains and Leaves in Homahills, Homabay County - Akenga, T.; Sudoi, V.; Kerich, E.; Machuka, W.; Ronoh, E. (African Journal of Education,Science and Technology (AJEST), 2019)
A single basis of heavy pollution may have severe impact on the health of human beings. Heavy metals go into the body system through air, food along with water and some bio-accumulate over a time period. The uptake of heavy metals by plants such as maize (Zea mays) is a path of their way into the human food chain. Pollution of animal feedstuffs with heavy metals can cause negative impacts to animal health and can cause harmful effects to humans through food chain such as consumption of meat and milk products. For that reason, monitoring uptake of excess heavy metals in Zea mays grains and leaves is paramount in avoiding unnecessary exposure. Therefore, this study sets out to determine heavy metal uptake in Zea mays grains as well as leaves in diverse agro-ecological regions farms in Homa Bay County. The average concentrations of Zn, Cd, Cu, Co and Pb in Zea mays grains were 0.113, 0.225, 0.122, 0.042 and 0.324 mg/kg respectively and that of maize leaves were 0.119, 0.041, 0.115, 0.041 and 0.321 mg/kg, respectively. The average concentration levels of Zn, Co and Cu were within the acceptable FAO/WHO standards for both Zea mays grains and leaves except Cd and Pb which were slightly above. The maize grains of the research area are quite secure for consumption. Regular monitoring for these metals in food is vital in ensuring consumption of safe food and avoids bioaccumulation in the food chain.